Two-Mode Wigner Operator in <η| Representation - Wu, He-Jun; Fan, Hong-Yi (Modern physics letters. B, Condensed matter physics, statistical physics, applied physics, 1997)
We derive the <η| representation of two-mode Wigner operator, where the <η| state is the common eigenstate of two particles' relative position and total momentum. By virtue of this representation we can conveniently obtain Wigner functions of some two-mode states and the Weyl correspondence functions of two-mode unitary phase operators.